2012
DOI: 10.2139/ssrn.2004264
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Health Events on Individual Labor Market Histories: The Message from Difference-in-Differences with Exact Matching

Abstract: erudite and tepp and Christine LE CLAINCHE y centre d' études de l' emploi lameta UMR 5474 ENS Cachan

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
8
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 10 publications
0
8
0
Order By: Relevance
“…These results support previous research that health selection is present in the causal relationship between health and labour force participation. 4,6,8,9,23,34,35 There was no statistically significant evidence of a different relative association of health shock with change in labour force status by sex and age.…”
Section: Discussionmentioning
confidence: 92%
See 4 more Smart Citations
“…These results support previous research that health selection is present in the causal relationship between health and labour force participation. 4,6,8,9,23,34,35 There was no statistically significant evidence of a different relative association of health shock with change in labour force status by sex and age.…”
Section: Discussionmentioning
confidence: 92%
“…However, most studies have shown that the health selection pathway is stronger than the social causation pathway when looking at the causal relationship between health and labour force participation. 6,23,34 A number of studies have found a (subjective) health shock was more likely to precipitate an exit from the labour force into early retirement or other reasons (e.g. into parenthood, receiving disability benefits and even late life education) rather to unemployment.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations